Oxidative damage to DNA, expression of Mt-1, and activation of repair mechanisms induced by vanadium trioxide in cultures of human lymphocytes - V.A. Alcántara-Mejía; A.A. Beltrán-Flores; R.A. Mateos-Nava; L. Álvarez-Barrera; I.U. Bahena-Ocampo; E. Santiago-Osorio; E. Bonilla-González; J.J. Rodríguez-Mercado (Toxicology Reports)
Vanadium (V) has garnered attention due to its pharmacological properties; however, its toxic effects have also been documented. Among the vanadium compounds that are found in the environment, vanadium trioxide (V2O3) has attracted interest because of its impact on biomolecules such as DNA, RNA, and proteins. However, its precise mechanism of action remains unclear, although it is suspected to be related to oxidative stress. Therefore, this study aimed to determine the mechanisms involved in DNA damage and the associated cellular response pathways. Primary cultures of human lymphocytes were exposed to 2, 4, 8, or 16 µg/mL V2O3. DNA damage due to oxidized bases was evaluated via a comet assay. The expression levels of sensor proteins (ATM and ATR) involved in DNA damage were determined via Western blotting, and the mRNA expression levels of metallothionein 1 (Mt-1) and genes involved in DNA repair (OGG1, APE1, XPB, XPD, MRE11, RAD50, Ku70, and Ku80) were estimated via RT-PCR and qPCR. The results showed that V2O3 is an oxidant that is responsible for DNA damage through oxidized bases, as demonstrated by increased DNA migration in the presence of the FPG enzyme. At the molecular level, V2O3 treatment also increased ATM protein expression. In terms of mRNA expression, the overexpression of Mt-1, OGG1, APE1, Ku70, and Ku80 was observed. This finding suggests that DNA damage is primarily repaired via two mechanisms: base excision repair (BER) and nonhomologous end joining (NHEJ). In conclusion, one mechanism of action of V2O3 involves the oxidation of nitrogenous bases in DNA, the activation of damage sensors (such as ATMs), and the overexpression of Mt-1 as part of the antioxidant response to mitigate the effects of V and facilitate DNA repair pathways (including BER and NHEJ).